The extrinsic factors affecting food preferences among Generation Y / Nurul Aida Samsudin ... [et al.] - Samsudin, Nurul Aida; Tamby Chik, Chemah; Azman, Farah Nurshaheera; Bachok, Sabaianah (UiTM Press, 2017)
Diet related diseases are due to poor food selection, and changes in lifestyle and these include cardiovascular disease and obesity. The prevalence of obesity in Malaysia had doubled up in the last decade, and this has affected general health and lifestyle of Malaysian. This study examined the main factors that influenced Generation Y’s food preferences in Malaysia. The survey had been conducted in Shah Alam and Puncak Alam, Selangor and had focused on three extrinsic factors; marketing, social and economic and food sensory attributes; as the influencing attributes for Generation Y food preferences. Two hundred fifty usable questionnaires had been used for analysis using SPSS version 20. Most of the respondents agreed that food sensory attributes (M = 4.080) are the main factor influencing their food preferences. Additionally, the results showed that food sensory attributes (β= .354) are the strongest attributes that influence Generation Y’s food preferences. The emphasis of producing food with high palatability has taken its toll on the society. Therefore specific measures need to be a plan to encounter this situation. This finding hoped to provide some input for government and food industry planning for future types of food that could resolve the obesity issues, especially among the younger generations.